Potential pests and diseases on Sari Intan snake fruit in Bintan Regency, Riau Islands, Indonesia - Melli Fitriani; Nina Maryana; Efi Toding Tondok (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Sari intan is a superior variety of snake fruit developed in Bintan District, Riau Islands, in 2015. The pests and diseases that attack the Sari Intan variety are not yet known. This research was conducted to analyze and identify potential pests and diseases affecting Sari Intan snake fruit at different plant ages in Bintan Regency. A survey was conducted in nurseries and in plantations with two- and five-year-old plant populations. Insects found were collected and identified in the laboratory. Plant parts showing disease symptoms were also collected; the pathogens were identified, and the intensity of damage was measured. Data were processed using Microsoft Office Excel 2010 and described qualitatively. The results showed that potential insect pests included Iceria sp. (Hemiptera: Monophlebidae), Coccotrypes sp. (Coleoptera: Curculionidae), and Setothosea asigna (Lepidoptera: Limacodidae). A non-insect pest observed was Zonitoides arboreus (Stylommatophora: Gastrodontidae). The incidence of disease in Sari Intan snake fruit leaves reached 100%, with a damage intensity of 58,7%, caused by fungal infections. The fungi identified were Pestalotia sp., Colletotrichum sp., Helminthosporium sp., Fusarium sp., and Curvularia sp. An important postharvest disease was fruit rot, caused by Thielaviopsis paradoxa.